Isolation and characterization of the mink interferon-epsilon gene and its antiviral activity - Zhang, Hailing; Zhang, Dongliang; Zhang, Shasha; Liu, Hao; Wang, Han; Wang, Cong; Zou, Deying; Hu, Bo; Lian, Shizhen; Lu, Shiying; Bai, Xue (Frontiers in Veterinary Science, 2023)
The interferon (IFN) response is the first line of defense against viral invasion and thus plays a central role in the regulation of the immune response. IFN-epsilon (IFN-ε) is a newly discovered type I IFN that does not require viral induction, unlike other type I IFNs. IFN-ε is constitutively expressed in epithelial cells and plays an important role in mucosal immunity. In this study, we evaluated the biological activity of the mink-IFN (MiIFN)-ε gene in prokaryotic cells. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used to evaluate IFN-ε expression in different mink tissues. MiIFN-ε was highly expressed in brain, lung, tracheal, kidney, intestinal, bladder, ovarian, and testis tissues. There was no significant difference in MiIFN-ε expression between female and male minks, except in the reproductive system. Expression of the small ubiquitin-like modifier (SUMO3)-MiIFN-ε fusion gene was induced by isopropylβ-d-thiogalactoside, and MiIFN-ε was collected after SUMO-specific protease digestion. We tested the antiviral activity of MiIFN-ε against vesicular stomatitis virus (VSV) in epithelial cells of feline kidney 81 (F81). We used qRT-PCR to analyze the expression of several IFN-stimulated genes (ISGs), including ISG15, 2′-5′ oligoadenylate synthetase (2′-5′OAS1), and myxovirus resistance protein 1 (Mx1). Recombinant IFN-ε induced high ISG expression in F81 cells. Compared with those in the cell control group, expressions of ISG15, Mx1, and 2′-5′ OAS1 in the VSV-GFP control, IFN-ε, and MiIFN-ε-inhibited VSV-GFP groups were significantly increased. Compared with those in the VSV-GFP control group, expressions of ISG15 and 2′-5′ OAS1 in the IFN-ε and MiIFN-ε-inhibited VSV-GFP groups were significantly increased, and the differences were highly significant (p < 0.0001). IFN-ε played an indirect antiviral role. These findings lay the foundation for detailed investigation of IFN-ε in the future.